INNOVATION OF THE EDUCATION PROCESS TOWARDS IMPLEMENTING AI TOOLS - Petra Mikulcová; Kristína Medeková; Drahoslav Lančarič; Radovan Savov (Trendy v podnikání)
Artificial intelligence (AI) is transforming education by offering personalized learning experiences, breaking traditional barriers, and preparing students for the future workforce. It enhances adaptability to modern educational demands and business trends while empowering both students and educators through innovative tools and methods. Our paper examines students' perceptions of AI and maps how they utilize AI tools, highlighting their role in meeting the challenges of today's educational and professional life. By analysing data collected through a structured questionnaire, we identified key themes, including the usefulness, ease of use, attitudes, and concerns surrounding AI. These findings serve as a foundation for understanding the role of AI in education and its potential to enhance learning experiences and adaptability to future challenges. The Kruskal-Wallis tests revealed significant differences in students' perceptions and use of AI based on demographic factors such as gender, study level, socioeconomic status, and place of residence. Female students reported greater difficulty using AI, highlighting the influence of historical gender stereotypes surrounding technology. Master’s students, likely due to their advanced academic exposure, demonstrated higher confidence and a stronger inclination to use AI for learning. Socioeconomic background and urban residency were linked to more supportive attitudes toward AI integration in education and privacy concerns. Additionally, students further along in their academic journey reported more frequent use of AI tools for language learning.